Some Gloomy Thoughts Concerning Cross-Border Insolvencies - Douglass G. Boshkoff (Washington University Law Quarterly, 1994)
In this Article, I: (1) briefly discuss the avenues of cooperation available when Nation B is the United States; (2) assess the current level of cooperation with Nation A; and (3) speculate whether the situation is likely to change in the foreseeable future.
Keywords: Bankruptcy; International; United States; International bankruptcy